2020
DOI: 10.3390/coatings10030204
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Optical Properties of Amorphous SnO2:Ta Films, Prepared by DC and RF Magnetron Sputtering: A Systematic Study of the Influence of the Type of the Reactive Gas

Abstract: By reactive magnetron sputtering from a ceramic SnO2:Ta target onto unheated substrates, X-ray amorphous SnO:Ta films were prepared in gas mixtures of Ar/O2(N2O, H2O). The process windows, where the films exhibit the lowest resistivity values, were investigated as a function of the partial pressure of the reactive gases O2, N2O and H2O. We found that all three gases lead to the same minimum resistivity, while the width of the process window is broadest for the reactive gas H2O. While the amorphous films were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…2a, the raise in carrier density contributes largely to the significant decrease of resistivity from 1.21 to 1.17 × 10 −3 Ω cm, corresponding to an increase of conductivity from 0.82 for SnO 2 to 855.0 S cm −1 for Sn 0.98 Ta 0.02 O 2 . Such conductivity relatively surpasses that of TTO films grown by spray pyrolysis [27], sputterings [33][34][35], and atomic layer deposition (ALD) [36]. Nevertheless, the carrier concentration gradually saturates with the Ta doping level change, and starts to decline slightly to 2.0 × 10 20 cm −3 at x = 0.03, probably due to the introduction of non-activated Ta (or compensating effect at higher Ta doping).…”
Section: Electrical and Optical Properties Of The Tto Thin Filmsmentioning
confidence: 97%
“…2a, the raise in carrier density contributes largely to the significant decrease of resistivity from 1.21 to 1.17 × 10 −3 Ω cm, corresponding to an increase of conductivity from 0.82 for SnO 2 to 855.0 S cm −1 for Sn 0.98 Ta 0.02 O 2 . Such conductivity relatively surpasses that of TTO films grown by spray pyrolysis [27], sputterings [33][34][35], and atomic layer deposition (ALD) [36]. Nevertheless, the carrier concentration gradually saturates with the Ta doping level change, and starts to decline slightly to 2.0 × 10 20 cm −3 at x = 0.03, probably due to the introduction of non-activated Ta (or compensating effect at higher Ta doping).…”
Section: Electrical and Optical Properties Of The Tto Thin Filmsmentioning
confidence: 97%
“…During the past two decades, SnO 2 :Ta (TTO) thin lms were deposited using many different techniques on different substrates. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] They showed charge carrier mobilities and resistivities competitive with those of ITO. The best values of up to 130 cm 2 (Vs) −1 and down to 1.1 × 10 −4 U cm, respectively, were obtained when pulsed laser deposition was used.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary optical data published in a recent book chapter were promising. 18 Moreover, while XRD is used as a standard technique for structure analysis of SnO 2 :Ta, [19][20][21][22][23][24][25][26][27][28][29][31][32][33][34][35][36] only two papers discussed Raman data of the material. 33,35 Mientus et al 33 stated that they observed weak, broad features in the Raman spectra of as-deposited SnO 2 :Ta lms and ascribed them to the glass substrate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations